PERAN MEDIASI EFIKASI DIRI PADA PENGARUH TUTOR SEBAYA TERHADAP KETERAMPILAN KOLABORASI SISWA MANAJEMEN PERKANTORAN DI SMKN 3 JAKARTA - Apriliana Dian Fadillah; Dedi Purwana; Maulana Amirul Adha (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the mediating role of self-efficacy in the relationship between peer tutoring and collaboration skills among Office Management students at SMK Negeri 3 Jakarta. A quantitative explanatory approach with a survey method was applied. The sample consisted of 118 students drawn from a population of 174 through proportional random sampling based on the Krejcie and Morgan table. Data were collected using a Likert-scale questionnaire and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS. The results show that peer tutoring has a positive and significant effect on self-efficacy (β = 0.793; p = 0.000), peer tutoring has a positive and significant effect on collaboration skills (β = 0.397; p = 0.000), self-efficacy has a positive and significant effect on collaboration skills (β = 0.478; p = 0.000), and self-efficacy partially mediates the effect of peer tutoring on collaboration skills (β = 0.379; p = 0.000). The model explains 68.7% of the variance in collaboration skills and 63.0% of the variance in self-efficacy. These findings confirm the importance of strengthening self-efficacy as a psychological bridge that optimizes the effect of peer tutoring on vocational students' collaboration skills. Keywords: peer tutoring, self-efficacy, collaboration skills, PLS-SEM, vocational students